Negative active material particles encapsulated in pyrolytic nanostructured metal oxides and methods of making and using same

By using the dry mixing method of nanostructured metal oxide prepared by pyrolysis and Si-based particles in lithium-ion batteries, a uniform coating is formed, which solves the problems of aging of Si-based negative electrode materials and poor dispersion of nano-oxides, and improves the battery cycle performance and lifespan.

CN119318029APending Publication Date: 2025-01-14EVONIK OPERATIONS GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380044716.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-05-24
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, Si-based negative electrode materials are prone to form uncontrolled solid electrolyte interfaces (SEIs) during charging and discharging, resulting in material aging and performance losses, and poor dispersion of nano-sized metal oxide particles leads to uneven coatings. , affects battery life.

Method used

Nanostructured metal oxides prepared by pyrolysis, such as alumina or titanium oxide, are mixed with carbon and/or Si-based particles under shear conditions by dry mixing to form a uniform metal oxide coating and pass through the surface Modification improves the coverage and dispersion of the coating.

Benefits of technology

The surface of the negative electrode material is uniformly covered, which improves the cycle performance and life of the battery, inhibits the formation of SEI, and enhances the electrochemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005167186540000211
    Figure BDA0005167186540000211
  • Figure BDA0005167186540000221
    Figure BDA0005167186540000221
  • Figure BDA0005167186540000231
    Figure BDA0005167186540000231
Patent Text Reader

Abstract

The invention relates to a method for producing a coated active anode material, in which a mixed anode material and a nanostructured and preferably surface-modified alumina, titanium oxide prepared by pyrolysis, or a mixture thereof are dry-mixed by means of a mixing unit having a specific electric power of 0.05 to 1.5 kW per kg of the mixed anode material. The coated mixed negative electrode material is obtained by the method. A negative electrode for a lithium ion battery and a lithium ion battery comprising such a coated active negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing encapsulated negative electrode active material particles, wherein carbon and / or Si-based particles and fumed nanostructured metal oxides are dry mixed under shear conditions. The present invention further relates to fumed metal oxide coated negative electrode materials and battery cells containing encapsulated carbon and / or Si-based negative electrode particles and their use. Background Art

[0002] Various energy storage technologies have recently attracted widespread public attention and have been the subject of intensive research and development in industry and academia. As energy storage technology is extended to devices such as cellular phones, camcorders, and notebook PCs, and further to electric vehicles, the demand for high energy density batteries used as power sources for such devices is increasing. Secondary lithium-ion batteries are one of the most important types of batteries currently in use.

[0003] Secondary lithium-ion batteries are usually composed of a negative electrode made of carbon materials or lithium-metal alloys, a positive electrode made of lithium-metal oxides, and an electrolyte in which lithium salts are dissolved in an organic solvent. The separator of a lithium-ion battery provides a lithium ion channel between the positive and negative electrodes during the battery's charge and discharge processes.

[0004] US2019 / 0393543 describes a lithium metal secondary battery comprising a positive electrode, a negative electrode and a porous separator or electrolyte arranged between the positive electrode and the negative electrode, wherein the negative electrode comprises: (a) a negative electrode active layer containing lithium or lithium alloy layers in the form of foil, coating or multiple particles aggregated together as the negative electrode active material; and (b) a negative electrode protective layer of a conductive sulfonated elastomer composite material arranged between the negative electrode active layer and the separator / electrolyte.

[0005] US2019 / 363345 describes forming a graphene protective coating on a negative lithium metal electrode for use in a lithium-containing electrochemical cell, such as a lithium-ion battery. The graphene protective coating is said to reduce dendrite formation and growth.

[0006] WO 2019 / 215406 A1 describes a negative electrode for a lithium-ion battery, comprising at least one negative electrode material which is binder-free, pre-charged with lithium ions, and coated with a protective coating comprising a very long list of allegedly suitable materials, however the coating used in the present invention is not disclosed in WO 2019 / 215406 A1.

[0007] CN 106025242 A describes a composite negative electrode material for lithium ion batteries, which comprises a core layer of porous silicon alloy nanowires with carbon nanotubes and a shell layer made of a conductive polymer film blended with polypropylene oxide, polyethylene succinate, polyethylene succinate or polyethylene glycol imine and graphene.

[0008] It is known to coat the positive electrode materials of lithium ion batteries with Al2O3, TiO2, ZrO2 to improve their cycle performance.

[0009] Examples of using metal oxides in positive electrode materials are provided in the following articles. In the article "mesoporous carbon material as cathode for high performance lithium-ion capacitor" published by Zhang et al. in Chinese Chemical Letters (2018), 29 (4) 620-623, Mg citrate is used as a precursor for C mesopores, and nano-sized metal oxide particles are used as templates provided by Mg citrate.

[0010] In the article “Improvement of cycling performance of lithium-sulfur batteries by using metal oxide as a functional additive for trapping lithium polysulfide” published by Ponraj et al. in ACS Applied Material Interfaces 2016, 8, 4000-4006, hydrophilic metal oxides were used as additives on the active sulfur surface of the cathode to trap polysulfides.

[0011] Elements like carbon and its allotropes (graphene) have been used as negative electrode materials in lithium-ion secondary batteries, however, there are several problems with the structural stability of graphene in the negative electrode. In the article "An electrode comprising of graphene nano-powder inserted in an enclosed structure in anodic aluminum oxide coated with PANI by using low temperature hydrothermal process" published by Sugam et al. in 1942, 62nd DAE Solid State Physics Symposium, 2017, graphene nanopowder was inserted and confined in the negative electrode aluminum oxide coated with PANI (polyaniline).

[0012] In the article “Analumina-coated Fe3O4-Reduced graphene oxide composite electrode as a stable anode for lithium-ion battery” published by Qi-Hui et al. in Electrochimica Acta 2015, 156, 147-153, Al2O3 coating was used on Fe3O4 reduced graphene oxide composite negative electrode material.

[0013] CN 104 393 258 discloses oxide-coated Si titanium alloys (graphene nanocomposites).

[0014] Wu Xin et al. described a one-step hydrothermal method to produce core-shell structures based on MgFe2O4 and TiO2 in “Electrochemical studies of MgFe2O4@TiO2 core-shell nanospheres as anodematerial for lithium battery applications” published in Journal of Materials Science: Science in Electronics, vol. 29, no. 20 (2018), pages 17872-17880, ISSN: 0957-4522.

[0015] A fairly common problem of negative electrode materials, especially Si-based negative electrode materials, is the formation of an uncontrolled solid electrolyte interface (SEI) during the initial charge-discharge process of the battery. In addition, aging processes within the bulk of the material lead to a loss of performance during cycling. This aging phenomenon is particularly relevant to Si-based negative active materials. During cycling, negative electrode materials are subject to several electrochemical degradation mechanisms that may lead to the deactivation of negative electrode materials. Electrolyte-induced surface transformations and undesirable side reactions with lithium species lead to the formation of an SEI layer with increased thickness, ultimately leading to reduced performance and battery life.

[0016] Surface coating has been demonstrated to be an extremely important approach to address this aging problem by inhibiting direct contact between the active material surface and the liquid electrolyte.

[0017] Although nano-sized metal oxide particles have been used as additives in lithium-ion batteries, their effectiveness is limited by poor dispersibility. Therefore, practical methods for improving the long life of secondary lithium-ion batteries are generally limited. Typically, the use of commercially available nano-sized metal oxides results in uneven distribution and large agglomerated metal oxide particles on the surface of the negative electrode material. As a result, the negative electrode material particles are not completely covered by the metal oxide particles, and there are large undispersed metal oxide particles, located near the negative electrode particles, and clearly visible by SEM elemental mapping.

[0018] The problem addressed by the present invention is to provide a uniform coating of a metal oxide or a metal oxide mixture around a negative electrode active material comprising carbon and / or Si-based particles.

[0019] In the course of comprehensive experiments, it was surprisingly found that pyrolytically prepared nanostructured metal oxides of aluminum oxide or titanium oxide (or mixed metal oxides of aluminum oxide and titanium oxide) can be successfully used to coat negative electrode materials including carbon and / or Si-based particles using a dry blending method for coating metal oxides on negative electrode materials. It was also surprisingly found that further surface modification of the pyrolytically prepared nanostructured metal oxides before dry blending can further significantly improve the coverage and uniformity of the coating. Summary of the invention

[0020] The present invention provides a method for preparing a coated active negative electrode material, the coated active negative electrode material, and the use of the coated active negative electrode material in a lithium ion battery. The lithium ion battery of the present invention can be used in electronic and electrical equipment, including, for example, mobile phones, computers (laptop computers, desktop computers, computer tablets), electronic watches, key fabs, electrical appliances, power tools, vacuum cleaners, electric lawn mowers, and electric vehicles.

[0021] According to a first aspect of the present invention, there is provided a method for preparing a coated active negative electrode material. The method is characterized in that the coated active negative electrode material is obtained by subjecting the active negative electrode material and a metal oxide of aluminum oxide or titanium oxide prepared by pyrolysis to dry mixing under shearing conditions in a mixing unit, characterized in that the coated active negative electrode material is in the form of particles and the metal oxide has a particle size of 5 to 300 m 2 The BET surface area of ​​the particles is 5 wt % and the mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution is measured by static light scattering (SLS) after ultrasonic treatment at 25° C. for 60 seconds, and the average aggregate diameter d 50 5 to 150 nm.

[0022] The pyrolytically prepared metal oxide is hydrophilic. Preferably, in one embodiment, the pyrolytically prepared metal oxide is surface modified to become hydrophobic.

[0023] In one embodiment, the hybrid unit has a specific electrical power of 0.05 to 1.5 kW per kg of mixed negative electrode material.

[0024] The coated active negative electrode material is in the form of particles, and the metal oxide has a particle size of 5 to 300 m 2 The BET surface area of ​​the particles is 5 wt % and the mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution is measured by static light scattering (SLS) after ultrasonic treatment at 25° C. for 60 seconds, and the average aggregate diameter d 50 It is 5 to 150 nm, more preferably 10 to 120 nm, even more preferably 20 to 100 nm.

[0025] The SEM-EDX profile of the coated active negative electrode material provides complete and uniform coverage of the metal oxide around substantially all negative electrode particles, with no or only very few larger metal oxide agglomerates.

[0026] In one embodiment, the method is characterized in that the specific electrical power of the mixing unit is 0.1 to 1000 kW and the volume of the mixing unit is 0.1 L to 2.5 m 3 , and the speed of the mixing tool in the mixing unit is 5 to 30 m / s.

[0027] The span (d ) of the particles of the metal oxides and / or the particles of the mixed oxides comprising aluminum or titanium, measured by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25° C. for 60 seconds. 90 -d 10 ) / d 50 0.4 to 1.2.

[0028] In one embodiment, the active negative electrode material is in powder form and comprises carbon particles, silicon particles, or silicon oxide particles, or any combination thereof.

[0029] The active negative electrode material comprises carbon and / or Si-based particles. As used herein, the term "Si-based particles" refers to silicon particles (e.g., pure silicon particles), silicon oxide (SiOx) particles, and any combination of silicon, silicon oxide and carbon particles, including mixtures and composites thereof. Silicon oxide can be SiO and / or SiO2.

[0030] In one embodiment, the coated active negative electrode material is further subjected to heat treatment after dry mixing.

[0031] In one embodiment, the proportion of the metal oxide in the coated active negative electrode material is 0.05 to 5 wt % based on the total weight of the coated mixed negative electrode material.

[0032] Another aspect of the present invention relates to a coated active negative electrode material obtainable by the above-described method.

[0033] According to another aspect of the present invention, there is provided a coated active negative electrode material comprising an active negative electrode material and a coating of a nanostructured metal oxide prepared by pyrolysis on the surface of a mixed negative electrode material, wherein the coated active negative electrode material is in the form of particles and the metal oxide has a particle size of 5 to 300 m 2 The BET surface area of ​​the particles is 5 wt % and the mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution is measured by static light scattering (SLS) after ultrasonic treatment at 25° C. for 60 seconds, and has a unimodal and narrow particle size distribution, with an average aggregate diameter d 50 The nanostructured metal oxide prepared by pyrolysis is preferably surface treated to become hydrophobic by reacting the hydroxyl groups of aluminum oxide or titanium oxide with silane to form -O-Si-R groups. The metal oxide is hydrophilic or hydrophobic, preferably hydrophobic. The active negative electrode material is carbon, silicon, silicon oxide (SiOx) or any combination thereof, including a mixture and / or a composite of carbon, silicon and silicon oxide.

[0034] Other aspects of the present invention relate to active negative electrode materials for lithium ion batteries comprising the coated active negative electrode materials, further relate to lithium ion batteries comprising the coated active negative electrode materials, and further relate to the use of the coated active negative electrode materials in active negative electrode materials for lithium ion batteries.

[0035] Another aspect of the invention relates to a device powered by a lithium-ion battery.

[0036] The nanostructured metal oxides prepared by the flame method have a single peak and narrow particle size distribution and excellent dispersibility in the dry coating method of the negative electrode material. These particles lead to excellent interaction and proper adhesion to the negative electrode active material.

[0037] Furthermore, the additional surface modification of these particles leads to further improvements in the interaction and adhesion with the negative electrode active material. This results in complete deagglomeration of the metal oxide agglomerates and ultimately provides negative electrode active material particles that are completely and uniformly covered with the pyrogenically nanostructured and surface modified metal oxide.

[0038] It has been found that by using pyrolytically prepared nanostructured metal oxide particles in combination with a high intensity dry coating method, the method of the present invention results in significantly improved dispersibility and uniform coating of the metal oxide particles. During dry mixing, the applied shear forces (mixing) break up any metal oxide agglomerates into tiny aggregates, which have a very high tendency to settle on the surface of the negative electrode active material particle powder, resulting in very good interaction and adhesion, which in turn leads to uniform coating. In contrast, conventional metal oxide particles, which are not pyrolytically prepared and nanostructured) consist of isolated spherical particles (which are the result of grinding coarser metal oxide particles) and do not show this behavior.

[0039] These and other features and advantages of the present invention will become better understood from the following detailed description taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The laser diffraction particle size analyzer shows Alu C(a) and Particle size distribution of AO-802(b).

[0041] Figure 2 The SEM-EDX (scanning electron microscopy combined with energy dispersive X-ray) images of different coating additives on the composite Si / C negative electrode active material DXB8 are shown (a: Alu C 805,b: Alu C,c: AO-802,d: TiO2T 805).

[0042] Figure 3 The SEM-EDX distribution of alumina coating additives on artificial graphite SAG20 is shown (a: Alu C 805,b: Alu C,c: AO-802).

[0043] Figure 4 A lithium-ion battery is shown within a device according to an embodiment of the present invention. DETAILED DESCRIPTION

[0044] According to a first aspect of the present invention, there is provided a method for preparing encapsulated active negative electrode material particles, wherein the active negative electrode material and the pyrogenic nanostructured metal oxide are dry mixed under shear conditions. The pyrogenic nanostructured metal oxide is also preferably surface modified to become hydrophobic before dry mixing. A second aspect of the present invention relates to a pyrogenic metal oxide coated negative electrode material, and a third aspect of the present invention relates to a battery cell containing encapsulated carbon and / or Si-based negative electrode particles.

[0045] Method for preparing coated negative electrode active material

[0046] According to a first aspect of the present invention, there is provided a method for preparing a coated active negative electrode material, wherein active negative electrode material particles such as carbon and / or Si-based negative electrode particles are dry mixed with pyrolytically prepared nanostructured and / or pyrolytically prepared mixed oxides comprising at least two metals under shear conditions. The Si-based negative electrode particles include silicon particles, silicon oxide particles, and any combination of silicon, silicon oxide and carbon particles.

[0047] The pyrogenically nanostructured metal oxide is also preferably surface modified to become hydrophobic prior to dry blending.

[0048] The active negative electrode material may also be referred to as core active negative electrode material or substrate active negative electrode material or particles. The pyrolytically prepared nanostructured and preferably surface-modified metal oxide may also be referred to as a coating. Coated active negative electrode material refers to a mixed active negative electrode material with a coating produced by dry mixing. Once dry mixing is completed, the carbon and / or Si-based particles are covered with the metal oxide.

[0049] Dry Mix

[0050] Dry mixing can be carried out, for example, in a mixing unit having a specific electrical power of 0.05 to 1.5 kW per kg of mixed negative electrode material. Dry mixing is understood to mean that no liquid is added or used during the mixing process, i.e., for example, substantially dry powders are mixed together. However, trace amounts of moisture or some liquid other than water may be present in the mixed raw materials, or these liquids may include water of crystallization.

[0051] If the specific electrical power used is less than 0.05 kW per kg of mixed negative electrode material, this produces an uneven distribution of metal oxides on the top of the negative electrode active material particles, which may not be firmly bound to the core material of the negative electrode active material particles. A specific electrical power greater than 1.5 kW per kg of mixed negative electrode material leads to poor electrochemical performance. In addition, there is a risk that the coating becomes brittle and easily breaks. The nominal electrical power of the hybrid unit can vary over a wide range, for example from 0.1 kW to 1000 kW. Therefore, a laboratory-scale hybrid unit with a nominal power of 0.1 to 5 kW or a production-scale hybrid unit with a nominal electrical power of 10 to 1000 kW can be used. The nominal electrical power is the maximum absolute electrical power nameplate of the hybrid unit.

[0052] The volume of the mixing unit can vary within a wide range. For example, the volume of the mixing unit can be from 0.1 L to 2.5 m 3 For example, a laboratory-scale mixing unit may have a volume of 0.1 to 10 L, and a production-scale mixing unit may have a volume of 0.1 to 2.5 m 3 volume.

[0053] Preferably, in the process according to the invention, the forced action mixer is used in the form of an intensive mixer with high-speed mixing tools. It has been found that the speed of the mixing tools is from 5 to 30 m / s, more preferably from 10 to 25 m / s, to obtain the best results. Examples of commercially available mixing units suitable for the process according to the invention include Henschel mixers and Eirich mixers. For example, the Eirich mixer can be a high-intensity Eirich mixer.

[0054] The mixing time may vary, preferably being from 0.1 to 120 minutes, more preferably from 0.2 to 60 minutes, and most preferably from 0.5 to 10 minutes.

[0055] After mixing, the mixture may be subjected to a heat treatment to improve the bonding of the coating to the negative electrode active material particles. However, this treatment is optional in the method according to the invention, because in this method, the nanostructured and surface-modified metal oxide prepared by pyrolysis adheres to the core negative electrode active material particles, i.e., carbon and / or silicon-based particles, with sufficient hardness. Therefore, a preferred embodiment of the method of the invention may not include a heat treatment after mixing.

[0056] It has been found that when the metal oxide has 5m 2 / g to 300m 2 / g, more preferably 10m 2 / g to 200m 2 / g and most preferably 15 to 150 m 2The best results regarding the adhesion of the metal oxide to the core negative electrode active material particles were obtained when the BET surface area was 1000 Å / g. The BET surface area can be determined according to DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller procedure.

[0057] Pyrolysis Formation

[0058] According to the metal oxide used in the method of the present invention, i.e. aluminum oxide or titanium oxide is pyrolytically prepared, i.e. prepared by pyrolysis. Pyrolysis is also referred to as " pyrolysis (fumed) " method. This " pyrolysis " or " pyrolysis " method relates to the reaction of the corresponding metal precursor in flame hydrolysis or the flame oxidation in oxyhydrogen flame to form metal oxide. The reaction initially forms highly dispersed approximately spherical primary metal oxide particles, which coalesce to form aggregates in the further process of reaction. Aggregates can then be aggregated into agglomerates. Different from the agglomerates that can be separated into aggregates relatively easily by introducing energy usually, aggregates are further decomposed only by strongly introducing energy if any. The metal oxide powder can be partially destroyed and converted into particles that are conducive to nanometer (nm) scope of the present invention by suitable grinding.

[0059] The preparation of pyrogenic metal oxides is further described in WO 2004 / 108595 A2. The pyrogenic metal oxides of the present invention include aluminum oxide (Al2O3), also known as alumina, and titanium oxide (TiO2), also known as titania. Preferably, the pyrogenic aluminum oxide and the pyrogenic titanium oxide are further subjected to a surface treatment to become hydrophobic. An example of a commercially available pyrogenic aluminum oxide is Alumina® from Evonik Operations. Alu C. Another example of a pyrogenic hydrophobic alumina is available from Evonik Operations Alu C 805. Examples of pyrogenic hydrophobic titanium oxides are commercially available from Evonik Operations. TiO2T 805. The BET surface areas and other properties of these materials are provided in Table 1.

[0060] More specifically, the aluminum oxide or titanium oxide powder prepared by pyrolysis, especially flame hydrolysis, can be prepared starting from a metal halide, preferably a metal chloride such as aluminum chloride or titanium chloride, respectively. The metal chloride precursor and, if applicable, other metal precursors can be evaporated, the resulting vapors being mixed with other gases alone or together with a carrier gas such as nitrogen in a mixing unit in a burner; i.e. air, oxygen, nitrogen and hydrogen. The gases are reacted with one another in a flame in a closed combustion chamber to produce a metal oxide (or mixed metal oxide) and an exhaust gas. The hot exhaust gas and the metal oxide are then cooled in a heat exchanger unit, the exhaust gas is separated from the metal oxide, and any halide residues adhering to the obtained metal oxide are removed by heat treatment with humidified air.

[0061] A flame spray pyrolysis (FSP) process suitable for preparing metal oxides may comprise the following steps:

[0062] 1) atomizing a solution containing a metal precursor (e.g., aluminum oxide chloride or titanium chloride), e.g., with the aid of air or an inert gas, preferably using a multi-substance nozzle, and

[0063] 2) mixed with combustion gases, preferably hydrogen and / or methane and air, and

[0064] 3) allowing the mixture to burn in a flame into a reaction chamber surrounded by a shell,

[0065] 4) Cooling the hot gases and solid products and then removing the solid products from the gases.

[0066] Suitable other aluminum oxide or titanium oxide metal precursors for preparing aluminum oxide or titanium oxide by flame spray pyrolysis may include inorganic compounds, such as nitrates, chlorides; or organic compounds, such as carboxylates of aliphatic acids having 6 to 9 carbon atoms, such as 2-ethylhexanoic acid aluminum or 2-ethylhexanoic acid titanium. The metal oxide precursor used can be atomized and dissolved in water or an organic solvent. Suitable organic solvents include methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, 2-acetone, 2-butanone, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, C1-C8-carboxylic acids, ethyl acetate, toluene, petroleum and mixtures thereof.

[0067] The pyrolytically prepared nanostructured and surface-modified metal oxide used in the process according to the invention is in the form of aggregated primary particles, preferably having a numerical average aggregate diameter of 5 to 150 nm, more preferably 10 to 120 nm, even more preferably 20 to 100 nm as determined by transmission electron microscopy (TEM). The numerical average diameter can be determined by calculating the average size of at least 500 particles analyzed by TEM.

[0068] The average diameter of the agglomerates is generally 1 to 2 μm. These average values ​​can be measured by static light scattering (SLS) in a suitable dispersion, for example in an aqueous dispersion. Agglomerates and partial aggregates can be destroyed, for example, by grinding or ultrasonic treatment of the particles to produce particles with a smaller particle size.

[0069] After a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution was ultrasonically treated at 25° C. for 60 seconds, the average aggregate diameter d of the metal oxide was measured by static light scattering (SLS). 50 It is 5 to 150 nm, more preferably 10 to 120 nm, even more preferably 20 to 100 nm.

[0070] Therefore, the nanostructured and surface-modified metal oxide prepared by pyrolysis used in the method of the present invention is characterized by high dispersibility, i.e. the ability to form relatively small particles under gentle ultrasonic treatment. It is believed that the dispersion under such mild conditions is related to the conditions in the dry coating method. This means that the agglomerates of the metal oxide are destroyed in a similar manner to ultrasonic treatment during the mixing process of the present invention, and a uniform coating of negative electrode active material particles can be formed.

[0071] The span (d ) of the particles of the metal oxide and / or the mixed oxide containing the metal is measured by static light scattering (SLS) after a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution is treated with ultrasound at 25° C. for 60 seconds. 90 -d 10 ) / d 50 It is preferably 0.4 to 1.2, more preferably 0.5 to 1.1, and even more preferably 0.6 to 1.0.

[0072] Therefore, the pyrolytically prepared nanostructured metal oxide used in the method of the present invention is preferably characterized by a relatively narrow particle size distribution. This helps to obtain a high quality metal oxide coating on the surface of the transition metal oxide.

[0073] d value 10 d 50 and d 90 It is often used to characterize the cumulative particle size distribution of a given sample. For example, d 10 The diameter is 10% of the sample volume by less than d 10 The diameter of the particles, d50, is the diameter of the particles smaller than d 50 The diameter of the particles. 50 Also called the “volume median diameter” because it divides the sample equally by volume; d 90 90% of the sample volume is smaller than d 90The diameter of the particles when they are composed.

[0074] The metal oxides (aluminum oxide and / or titanium oxide) prepared by pyrolysis are hydrophilic. The hydrophobic metal oxide is then prepared by surface modification of the metal oxide prepared by pyrolysis. The surface treatment may include the use of any of many suitable hydrophobic agents, such as silanes. Using the method of the present invention, both the hydrophilic and hydrophobic forms of the pyro-nanostructured metal oxides can be used as coatings by dry mixing with the substrate active negative electrode material. However, pyro-nanostructured and surface-modified hydrophobic metal oxides are preferred because they show more uniform coverage of the substrate active negative electrode material and complete coverage of the substrate active negative electrode material.

[0075] Surface treatment of pyrolytically prepared metal oxides

[0076] Pyrolytically prepared aluminum or titanium oxide without any further surface treatment is hydrophilic because it is naturally covered with hydroxyl (–OH) groups. However, by surface modification of the pyrolytically prepared aluminum or titanium oxide, hydrophobic aluminum or titanium oxide can be prepared. For example, the hydrophobization of the aluminum or titanium oxide can be performed by reacting the hydroxyl groups with silanes to form –O–Si–R groups. Thus, preferably, the aluminum or titanium oxide is surface modified, which means that the surface of the aluminum or titanium oxide is at least partially covered with silanes.

[0077] Alumina or titanium oxide prepared by pyrolysis can be used in its hydrophilic and hydrophobic forms. The use of hydrophilic alumina or titanium oxide does not require any further treatment after synthesis by pyrolysis. However, by further treatment with a hydrophobic agent such as silane, the alumina or titanium oxide particles can be rendered hydrophobic after synthesis by pyrolysis. For example, in one embodiment, octylsilane is covalently bonded to the surface of the alumina or titanium oxide particles. Using the method of the present invention, both hydrophilic and hydrophobic forms of pyro-nanostructured alumina or titanium oxide can be effectively used as coatings by dry mixing with a substrate active negative electrode material. Pyro-nanostructured and surface-modified alumina or titanium oxide is preferred because it shows a more uniform coverage of the substrate active negative electrode material.

[0078] Thus, pyrolytically prepared aluminum oxide or titanium oxide is sprayed with a surface modifier at room temperature and the mixture is subsequently heat treated at a temperature of 50 to 300° C., preferably 80 to 180° C., for 0.5 to 3 hours.

[0079] In an alternative embodiment, surface modification of pyrogenically prepared aluminum or titanium oxide may be performed by treating the pyrogenic metal oxide with a surface modifier in vapor form and subsequently heat treating the mixture at a temperature of 50 to 800° C. for a period of 0.5 to 6 h.

[0080] An alternative method for surface modification of pyrogenically prepared aluminum oxide or titanium oxide may be carried out by treating the pyrogenic aluminum oxide or titanium oxide with the surface modifier in vapor form and subsequently heat treating the mixture at a temperature of 50 to 800° C. for a period of 0.5 to 6 h.

[0081] The heat treatment can be carried out under a protective gas such as nitrogen. The surface treatment can be carried out continuously or batchwise in a heatable mixer and dryer with a spray device. Suitable devices can be, for example, plowshare mixers or plates, cyclone separators or fluidized bed dryers.

[0082] The invention has the advantage that commercially available silanes can be used to modify the metal oxide, ie aluminium oxide or titanium oxide, and thus the properties of the aluminium oxide or titanium oxide can be individually adapted depending on the desired properties and the intended purpose.

[0083] As surface modifiers, the following compounds and mixtures of the following compounds may be used:

[0084] a)(RO)3Si(C n H 2n+1 ) and (RO)3Si(C n H 2n-1 ) type organosilanes, wherein R = alkyl, such as methyl, ethyl, n-propyl, isopropyl, butyl, and n = 1-20;

[0085] b) R' x (RO) y Si(C n H 2n+1 ) and R' x (RO) y Si(C n H 2n-1 ) type organosilane, wherein

[0086] R = alkyl, for example, methyl-, ethyl-, n-propyl-, isopropyl-, butyl-,

[0087] R' = alkyl, for example, methyl, ethyl, n-propyl, isopropyl, butyl,

[0088] R'=cycloalkyl,

[0089] n = 1-20,

[0090] x+y=3,

[0091] x = 1, 2, and

[0092] y = 1, 2;

[0093] c)X3Si(C n H 2n+1 ) and X3Si(Cn H 2n-1 ) type of halogenated organosilane, wherein

[0094] X=Cl, Br,

[0095] n = 1-20;

[0096] d)X2(R')Si(C n H 2n+1 ) and X2(R')Si(C n H 2n-1 ) type of halogenated organosilane, wherein

[0097] X=Cl, Br,

[0098] R' = alkyl, for example, methyl, ethyl, n-propyl, isopropyl, butyl,

[0099] R'=cycloalkyl,

[0100] n = 1-20;

[0101] e)X(R')2Si(C n H 2n+1 ) and X(R')2Si(C n H 2n-1 ) type of halogenated organosilane, wherein

[0102] X=Cl, Br,

[0103] R' = alkyl, for example, methyl, ethyl, n-propyl, isopropyl, butyl,

[0104] R'=cycloalkyl,

[0105] n = 1-20;

[0106] f)(RO)3Si(CH2) m -R' type organosilicon

[0107] R = alkyl, such as methyl, ethyl, propyl,

[0108] m=0,1-20,

[0109] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13, –O–CF2–CHF2, –NH2, –N3, –SCN, –CH=CH2, –NH–CH2–CH2–NH2, –N–(CH2–CH2–NH2)2, –OOC(CH3)C=CH2 , –OCH2–CH(O)CH2, –NH–CO–N–CO–(CH2)5, –NH–COO–CH3, –NH–COO–CH2–CH3, –NH–(CH2)3Si(OR)3, –S x –(CH2)3Si(OR)3, –SH, –NR'R”R”', among which

[0110] R'=alkyl, aryl,

[0111] R"=H, alkyl, aryl,

[0112] R"'=H, alkyl, aryl, benzyl, C2H4NR""R""', where R""=H, alkyl, and

[0113] R""'=H, alkyl;

[0114] g)(R") x (RO) y Si(CH2) m –R' type organosilicon

[0115] R"=alkyl,

[0116] x+y=2,

[0117] = cycloalkyl x = 1, 2,

[0118] y=1、2,

[0119] m=0,1-20,

[0120] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , –O–CF2–CHF2, –NH2, –N3, –SCN, –CH=CH2, –NH–CH2–CH2–NH2, –N–(CH2–CH2–NH2)2, –OOC(CH3)C=CH2 , –OCH2–CH(O)CH2, –NH–CO–N–CO–(CH2)5, –NH–COO–CH3, –NH–COO–CH2–CH3, –NH–(CH2)3Si(OR)3, –S x –(CH2)3Si(OR)3, –SH, –NR'R”R”', among which

[0121] R'=alkyl, aryl,

[0122] R"=H, alkyl, aryl,

[0123] R"'=H, alkyl, aryl, benzyl, C2H4NR""R""', where R""=H, alkyl, and

[0124] R""'=H, alkyl;

[0125] h)X3Si(CH2) m –R' type halogenated organosilanes

[0126] X=Cl, Br,

[0127] m=0,1-20,

[0128] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , –O–CF2–CHF2, –NH2, –N3, –SCN, –CH=CH2, –NH–CH2–CH2–NH2, –N–(CH2–CH2–NH2)2, –OOC(CH3)C=CH2 , –OCH2–CH(O)CH2, –NH–CO–N–CO–(CH2)5, –NH–COO–CH3, –NH–COO–CH2–CH3, –NH–(CH2)3Si(OR)3, –S x –(CH2)3Si(OR)3, –SH;

[0129] i)(R)X2Si(CH2) m –R' type halogenated organosilanes

[0130] X=Cl, Br,

[0131] R = alkyl, such as methyl, ethyl, propyl,

[0132] m=0,1-20,

[0133] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , –O–CF2–CHF2, –NH2, –N3, –SCN, –CH=CH2, –NH–CH2–CH2–NH2, –N–(CH2–CH2–NH2)2, –OOC(CH3)C=CH2 , –OCH2–CH(O)CH2, –NH–CO–N–CO–(CH2)5, –NH–COO–CH3, –NH–COO–CH2–CH3, –NH–(CH2)3Si(OR)3, –S x –(CH2)3Si(OR)3, –SH;

[0134] j)(R)2XSi(CH2) m –R' type halogenated organosilanes

[0135] X=Cl, Br,

[0136] R = alkyl,

[0137] m=0,1-20,

[0138] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , –O–CF2–CHF2, –NH2, –N3, –SCN, –CH=CH2, –NH–CH2–CH2–NH2, –N–(CH2–CH2–NH2)2, –OOC(CH3)C=CH2 , –OCH2–CH(O)CH2, –NH–CO–N–CO–(CH2)5, –NH–COO–CH3, –NH–COO–CH2–CH3, –NH–(CH2)3Si(OR)3, –S x –(CH2)3Si(OR)3, –SH.

[0139] Preferably, as surface modifiers, the following silanes are used alone or in a mixture: dimethyldichlorosilane, octyltrimethoxysilane, octyltriethoxysilane, hexamethyldisilazane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, dimethylpolysiloxane, glycidyloxypropyltrimethoxysilane, glycidyloxypropyltriethoxysilane, nanofluorohexyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, aminopropyltriethoxysilane. Particularly preferably, octyltrimethoxysilane and octyltriethoxysilane can be used.

[0140] The metal oxide particles prepared by pyrogenic methods generally have a purity of at least 96% by weight, preferably at least 98% by weight, more preferably at least 99% by weight. The metal oxide used in the process according to the invention preferably contains the elements Cd, Ce, Fe, Na, Nb, P in a proportion of <10 ppm and the elements Ba, Bi, Cr, K, Mn, Sb in a proportion of <5 ppm, wherein the sum of the proportions of all these elements is <100 ppm. The chloride content is preferably less than 0.5% by weight, more preferably 0.01 to 0.3% by weight, based on the mass of the metal oxide powder. The proportion of carbon in the hydrophilic non-surface-modified metal oxide is preferably less than 0.2% by weight, more preferably 0.005 to 0.2% by weight, even more preferably 0.01 to 0.1% by weight, based on the mass of the metal oxide powder.

[0141] Active negative electrode material

[0142] The substrate negative electrode particles encapsulated or coated with igneous metal oxides may include any suitable material used as a negative electrode active material in a lithium ion secondary battery, which can reversibly insert / deinsert lithium ions and / or reversibly react with lithium substances. Examples thereof are carbonaceous materials, including crystalline carbon, such as natural or artificial graphite in the form of plate-like, flaky, spherical or fibrous graphite; amorphous carbon, such as soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc., or mixtures thereof. In addition, Si-based particles can be used as negative electrode active materials. Preferred negative electrode active materials are carbon and / or Si-based particles. Si-based particles include silicon particles (e.g., pure silicon particles), silicon oxide (SiOx) particles, and any combination of silicon, silicon oxide and carbon particles, including mixtures and composites thereof. Silicon oxide can be SiO and / or SiO2. In one embodiment, the active negative electrode material can be a nanostructured porous silicon material. In one embodiment, the negative electrode material is SiOx, where x can be from 0 to about 2, such as Si, SiO, SiO2, or any combination thereof.

[0143] Preferred negative electrode active materials are carbon and / or Si-based particles, including composite materials of C and Si-based particles. "Composite material" refers to a composition comprising a carbon material and a silicon material. The carbon and silicon materials can be a mixture of carbon powder and silicon powder of nano-sized particles. In one embodiment, the composite material can include a single particle of chemically bonded carbon and silicon. In another embodiment, the composite material can include porous nano-sized silicon particles, wherein the carbon is impregnated in a silicon porous structure.

[0144] The active negative electrode material mixed and coated with metal oxides may include carbon and / or Si-based particles. In some embodiments, the active negative electrode material may include a composite SiOx / C material, wherein x may vary from 0 to about 2, made of 60 to 99% carbon and 40 to 1% silicon oxide, preferably 70 to 95% carbon and 30 to 5% silicon oxide, more preferably 80 to 90% carbon and 20 to 10% silicon oxide. The composite SiOx / C material may be in the form of a powder or granules.

[0145] In one embodiment, the active negative electrode material may include a composite SiO / C material made of 60 to 99% carbon and 40 to 1% SiO, preferably 70 to 95% carbon and 30 to 5% SiO, more preferably 80 to 90% carbon and 20 to 10% SiO. The composite SiO / C material may be in the form of powder or granules.

[0146] In some embodiments, the active negative electrode material may include a composite Si / C material made of 60 to 99% carbon and 40 to 1% silicon, preferably 70 to 95% carbon and 30 to 5% silicon, more preferably 80 to 90% carbon and 20 to 10% silicon. The composite Si / C material may be in the form of powder or granules.

[0147] The coated active negative electrode material has a numerical average particle size of 1 to 50 μm, preferably 1 to 40 μm, more preferably 2 to 20 μm. The numerical average particle size can be determined by laser diffraction particle size analysis according to ISO 13320:2009.

[0148] The active negative electrode material may also be referred to as a core active negative electrode material or a substrate active negative electrode material or particle. Titanium oxide or aluminum oxide may also be referred to as a coating, and the mixed active negative electrode material with the coating may also be referred to as a coated active negative electrode material or particle.

[0149] The proportion of the metal oxide in the coated mixed negative electrode material is preferably 0.05 to 5% by weight, more preferably 0.1 to 2% by weight, based on the total weight of the coated mixed negative electrode material. If the proportion of the metal oxide is less than 0.05% by weight, the beneficial effect of the coating is generally still not observed. In the case where it exceeds 5% by weight, the beneficial effect of the additional amount of the metal coating exceeding 5% by weight is generally not observed.

[0150] The coated mixed negative electrode material preferably has a coating thickness of 10 to 200 nm as determined by TEM analysis.

[0151] The present invention further provides a coated hybrid negative electrode material obtainable by the method of the present invention. The present invention further provides a coated hybrid negative electrode material comprising a pyrolytically prepared nanostructured and surface-modified metal oxide coating on the surface of the negative electrode active material particles.

[0152] In a preferred embodiment of the method according to the present invention, the further preferred features of the coated mixed negative electrode material of the above-mentioned pyrolytically prepared nanostructured and surface-modified metal oxide are also the preferred features of the coated mixed negative electrode material according to the present invention, the coated mixed negative electrode material of the pyrolytically prepared nanostructured and surface-modified metal oxide, regardless of whether it is prepared by the method of the present invention.

[0153] The present invention further provides an active negative electrode material for a lithium ion battery, comprising a coated negative electrode material according to the invention or a coated negative electrode material obtainable by a process according to the invention.

[0154] The negative electrode, i.e., the negative electrode of the lithium ion battery, includes a current collector and coated active negative electrode material particles formed on or above the current collector. The current collector can be aluminum foil, copper foil, nickel foil, stainless steel foil, titanium foil, a polymer substrate coated with a conductive metal, or a combination thereof.

[0155] The present invention also provides a lithium ion battery comprising a coated negative electrode material or a coated negative electrode material obtainable by the method according to the present invention.

[0156] In addition to the negative electrode, the lithium ion battery of the invention may also comprise a positive electrode, an optional separator and an electrolyte comprising, for example, a lithium salt or a lithium compound.

[0157] The positive electrode of the lithium-ion battery may comprise any suitable material that is commonly used in secondary lithium-ion batteries and is capable of reversibly intercalating / deintercalating lithium ions.

[0158] The cathode material preferably used in the method according to the invention is selected from lithium-cobalt oxide, lithium-manganese oxide, lithium-nickel-cobalt oxide, lithium-nickel-manganese-cobalt oxide, lithium-nickel-cobalt-aluminum oxide, lithium-nickel-manganese oxide or mixtures thereof.

[0159] The electrolyte of the lithium-ion battery can be in liquid, gel or solid form. The liquid electrolyte of the lithium-ion battery can include any suitable organic solvent commonly used in lithium-ion batteries, such as anhydrous ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate, ethyl methyl carbonate, diethyl carbonate, γ-butyrolactone, dimethoxyethane, fluoroethylene carbonate, vinyl ethylene carbonate or a mixture thereof.

[0160] The gel electrolyte includes a gelling polymer. Any suitable gelling polymer may be used.

[0161] Solid electrolytes for lithium-ion batteries may comprise oxides, such as lithium metal oxides, sulfides, phosphates, or solid polymers.

[0162] The electrolyte of a lithium-ion battery may contain a lithium salt. Examples of such lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis[2-(trifluoromethylsulfonyl)imide] (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium trifluoromethanesulfonate, LiN(SO2CF2CF3)2, and mixtures thereof.

[0163] The invention further provides for the use of the coated negative electrode material as an active negative electrode material for a lithium ion battery.

[0164] Even without further explanation, it is assumed that one skilled in the art can fully utilize the above description.Therefore, the preferred embodiments and examples should be construed as merely descriptive and not limiting in any way.

[0165] Hereinafter, the present invention is explained in more detail using examples.Alternative embodiments of the present invention can be obtained in a similar manner. DETAILED DESCRIPTION

[0167] Example

[0168] Determination of physicochemical characteristic data

[0169] In the context of the present invention, the following measurement methods for evaluating the properties of different materials are used:

[0170] A) BET surface area:

[0171] The BET surface area is determined with nitrogen according to DIN 9277:2014.

[0172] B) Compacted density:

[0173] The compacted density is determined according to DIN ISO 787 / XI.

[0174] Basic principles of tamped density determination:

[0175] The tamped density (formerly tamped volume) is equal to the quotient of the mass and volume of the powder after tamping in a tamped volumeter under predetermined conditions. According to DIN ISO 787 / XI, the tamped density is expressed in g / cm 3 However, since the tamped density of the oxide is very low, we give the value in g / L. In addition, the drying and sieving as well as the repetition of the tamping operation are omitted.

[0176] Equipment for tamping density determination:

[0177] Compacting capacity meter

[0178] Graduated Cylinder

[0179] Laboratory scale (read to 0.01g)

[0180] To perform a tamped density determination:

[0181] Fill the cylinder of the compaction volumetric instrument with 200 ± 10 mL of oxide so that there are no pores and the surface is flat. The mass of the filled sample is accurately determined to 0.01 g. Place the cylinder with the sample in the cylinder holder of the compaction volumetric instrument and tamp 1250 times. Read the volume of the compacted oxide accurately once.

[0182] Evaluation of compacted density determination

[0183]

[0184] C) pH value:

[0185] The pH values ​​were determined in a 4% aqueous dispersion of the hydrophobic oxide in water:methanol (1:1).

[0186] Reagents for pH determination:

[0187] Distilled water or completely deionized water, pH>5.5

[0188] Methanol, pa

[0189] Buffer, pH 7.00 pH 4.66

[0190] Equipment for pH determination:

[0191] Laboratory scale, (read to 0.1g)

[0192] Glass beaker, 250mL

[0193] Magnetic stirrer

[0194] Magnetic bar, 4 cm long

[0195] Combined pH Electrode

[0196] pH Measurement Equipment

[0197] Dispenser, 100mL

[0198] Procedure for determining pH value:

[0199] Adapt to DIN / ISO 787 / IX for determination of:

[0200] Calibration: Before determining the pH value, calibrate the measuring device with a buffer. If several measurements are carried out in succession, a single calibration is sufficient.

[0201] 4 g of hydrophilic oxide was mixed with 96 g (96 mL) of water in a 250 mL glass beaker using a dispenser to form a paste, and stirred with a magnetic stirrer for five minutes (rpm about 1000 min) while immersing a pH electrode. -1 ).

[0202] 4 g of hydrophobic oxide and 48 g (61 mL) of methanol were stirred into a paste in a 250 mL glass beaker. The suspension was diluted with 48 g (48 mL) of water and stirred with a magnetic stirrer for five minutes while immersing a pH electrode (rpm about 1000 min -1 ). After switching off the stirrer, read the pH after a one minute standing time. The result is given to one decimal place.

[0203] D) Loss on drying

[0204] In contrast to the 10 g weighing weight mentioned in DIN ISO 787II, a 1 g weighing weight is used for the drying loss determination.

[0205] The cover is put in place before cooling. No secondary drying is performed.

[0206] About 1 g of sample is weighed accurately to 0.1 mg, placed in a weighing dish with a floor lid dried at 105° C., avoiding the formation of dust, and dried in a drying cabinet at 105° C. for two hours.

[0207] After cooling in the desiccator with its lid still open, the sample was reweighed under the blue gel.

[0208]

[0209] The result is given to one decimal place.

[0210] E) Loss on ignition

[0211] Equipment for determining loss on ignition:

[0212] Porcelain crucible with crucible cover

[0213] Muffle furnace

[0214] Analytical scale (read to 0.1 mg)

[0215] Dryer

[0216] Loss on ignition:

[0217] In contrast to DIN 55 921, 0.3 to 1 g of undried substance is weighed accurately to 0.1 mg, placed in a porcelain crucible with a crucible cover which has been previously red-hot heated and red-hot heated in a muffle furnace at 1000° C. for 2 hours. Care must be taken to avoid the formation of dust. It has proven to be advantageous to place the weighed sample into the muffle furnace while the muffle is still cold. The slow heating of the furnace prevents the creation of stronger air turbulence in the porcelain crucible. After reaching 1000° C., red-hot heating is continued for a further 2 hours. Subsequently, the crucible cover is put in place and the weight loss of the crucible is determined on a blue gel in a desiccator.

[0218] Evaluation of loss on ignition determination

[0219] Since the LOI is measured relative to the sample dried at 105°C for 2 h, the following calculation formula is obtained:

[0220]

[0221] m0=weighing weight (g)

[0222] TV = Loss on drying (%)

[0223] m1 = weight of the sample after heating to red heat (g)

[0224] The result is given to one decimal place.

[0225] F) Carbon content

[0226] The carbon content is determined by elemental analysis using a LECO C744 instrument. The measuring principle is based on the oxidation of the carbon in the sample to CO2, which is then quantified by an infrared detector.

[0227] G) SEM measurement

[0228] Energy dispersive X-ray spectroscopy (EDX) was performed with a SEM. For the EDX profile, a representative area of ​​the sample was used at a magnification of 1000×, with an image width of 2048×1536 pixels (120μm×90.1μm), resulting in a pixel resolution of 0.059μm. The plots were recorded with an accelerating voltage of 20kV. After the measurement, the sum spectrum of the profile was used to determine the elements present in the sample. The threshold of the image analysis was adjusted according to the semi-quantitative mass % value of each element.

[0229] Starting Materials

[0230] Dry coating additives:

[0231] BET surface area is 85 to 115 m 2 / g of fumed alumina ( Alu C), commercially available from Evonik Operations. Alu C is a fine particle material, pure aluminum oxide (Al2O3) with a high specific surface area.

[0232] BET surface area 75 to 105 m 2 / g of pyrogenic hydrophobic alumina ( Alu C 805), commercially available from Evonik Operations. Alu C 805 is highly hydrophobized with organosilane.

[0233] BET surface area 35 to 55 m 2 / g of pyrogenic hydrophobic titanium oxide ( TiO2 T 805), commercially available from Evonik Operations. TiO2T805 is a fine particle fumed titanium oxide (TiO2) that has been highly hydrophobized using organosilane.

[0234] The BET surface area is about 6 m 2 / g non-pyrogenic alumina ( AO-802), commercially available through Admatechs Company Limited. AO-802 consists of microscopic spherical aluminum oxide particles with a diameter of 0.2 to 10 μm, which are prepared by oxidizing metallic aluminum powder using an original technique known as the VMC process.

[0235] Table 1 shows the overall properties of these materials.

[0236] Table 1:

[0237]

[0238] Negative electrode active material:

[0239] A composite Si / C material (DXB8) made of 86% carbon and 14% silicon purchased from Shandong Gelon Lib Co., Ltd., China, and artificial graphite powder (SAG20) purchased from MTI Corporation, USA were used.

[0240] Composite Si / C materials made of 86 wt% carbon and 14 wt% silicon are commercially available from Shandong Gelon Lib Co., Ltd., China under the trademark DXB8 and are hereinafter referred to as Si86 / C14 substrate negative electrode active material ("Si86 / C14_AAM") powder or particles. As shown in SEM analysis, Si86 / C14_AAM is a mixture of SiOx and carbon and has the following characteristics.

[0241]

[0242] The artificial graphite powder (SAG20) of MTI Corporation of the United States has the following characteristics.

[0243] D50μm 19.0-23.0 Moisture% ≤0.12 Carbon content% ≥99.50 <![CDATA[Compaction density (g / cm 3 )]]> ≥0.99 <![CDATA[SSA (Specific Surface Area) m 2 / g]]> ≤4.2

[0244] Embodiment 5-10

[0245] Two different types of negative active material powders (AAM) were mixed with respective amounts (1.0 wt%) of coating additives, namely Alu C (Example 1), and Alu C 805 (Example 2) and TiO2T 805 (Example 3) was mixed. Mixing was performed in a high intensity laboratory mixer (Somakon mixer MP-GL with 0.5 L mixing unit). For homogenization of both powders, the speed was increased stepwise: 1 min 100 rpm, 1 min 200 rpm, 1 min 500 rpm. After homogenization, the mixing speed was further increased to 2000 rpm for 5 min to achieve dry coating of the AAM particles by the corresponding metal oxide additive.

[0246] When using Alu C 805 and When TiO2 T 805 is used as a coating additive, uniformly coated AAM particles are obtained, with the thickness of the fumed metal oxide coating on top of the AAM particles being 20 to 200 nm.

[0247] Comparative Example 11

[0248] The steps of Examples 5-10 were repeated completely, with the only difference being that non-pyrogenic alumina was used. AO-802 replaces fumed metal oxides.

[0249] The particle size distribution of the hydrophilic alumina was measured to observe the dispersibility behavior during application of shear force to the alumina agglomerates.

[0250] Figure 1 The laser diffraction particle size analyzer shows Alu C(a) and Particle size distribution of AO-802(b). The samples were dispersed in distilled water and treated in an external ultrasonic bath (160 W) for 5 minutes.

[0251] for Alu C, a single peak and very narrow particle size distribution were detected with small aggregate sizes of D10 = 60 nm, D50 = 81 nm, and D90 = 120 nm.

[0252] exist In the case of AO-802, a broader, spread out and partially bimodal distribution was detected with aggregate sizes of D10 = 78 nm, D50 = 176 nm, D90 = 1770 nm, indicating the presence of larger, non-dispersed particles.

[0253] Figure 2 The SEM-EDX distribution of different coating additives on the composite Si / C negative electrode active material DXB8 is shown (a: Alu C 805,b: Alu C,c: AO-802,d: TiO2 T 805). On the left side of each of 2a, 2b, 2c, and 2d, an image of Si is shown to visualize the silicon distribution within the negative electrode active material (a mixture of carbon and silicon). This information helps to compare with the Al / Ti distribution of the coating additive on the right side and shows the interaction of the coating additive with the surface of the negative electrode material well.

[0254] The images of DXB8 coated with pyrogenic hydrophobic aluminum oxide (a) and pyrogenic hydrophobic titanium oxide (d) show complete and uniform coverage of Al / Ti around essentially all anode particles (silicon-rich as well as carbon-rich). No larger metal oxide agglomerates were detected, indicating that the dispersion of the nanostructured pyrogenic hydrophobic metal oxide was successful. In addition, no free, unattached Al2O3 / TiO2 particles were found in close proximity to the anode particles, indicating a strong interaction of the surface-modified metal oxide particles with the AAM particle surface, thus providing excellent adhesion between the coating and the substrate.

[0255] Compared to alumina, which is surface-modified and thus hydrophobic, hydrophilic materials ( Alu C) also shows good dispersion of aggregates, but preferentially interacts with Si-rich particles rather than carbon-rich particles. Thus, the alumina coating is more pronounced on the surface of the silicon-rich particles.

[0256] In contrast, by using coarser alumina particles ( AO-802) as a coating of AAM particles (c), only a small amount of finer sized Al2O3 particles are attached to the surface of the negative electrode material. Larger undispersed and therefore unattached Al2O3 particles are located near the negative electrode particles. As a result, the AAM particles are not completely covered by such rough non-surface-modified alumina particles.

[0257] Figure 3 The SEM-EDX distribution of alumina coating additives on artificial graphite SAG20 is shown (a: Alu C 805,b: Alu C,c: AO-802). In each of 3a, 3b, 3c, on the left is the material contrast.

[0258] Compared directly with hydrophilic alumina materials, pyrogenic hydrophobic alumina The profile of Alu C 805 coated graphite shows the best dispersion and most uniform coverage of the AAM particles by alumina. This phenomenon is again consistent with The hydrophobic surface modification of Alu C 805 is associated with the excellent interaction with the surface of graphite anode particles.

[0259] Figure 4 A lithium ion battery, generally indicated by the numeral 10, is shown within a device 100 powered by a lithium ion battery 10 according to one embodiment of the present invention. The device may be any electronic device, such as a mobile phone, an electronic watch, a keyboard, a laptop computer, a desktop computer, a computer keyboard, etc. The device may also be an electrical device such as a power tool, a vacuum cleaner, an electric lawn mower, an appliance, etc. As is well known, lithium ion batteries 10 may be packaged in modules, each module containing a plurality of lithium batteries 10, and used to power an electric vehicle or a hybrid electric vehicle. The lithium ion battery 10 comprises a negative current collector 14 and a positive current collector 12, a positive electrode 18 adjacent to the positive current collector 12, a negative electrode adjacent to the negative current collector 14, an electrolyte 20, and a separator 22 disposed between the negative electrode 16 and the positive electrode 18. The negative electrode 16 comprises a coated active negative electrode material obtained by dry mixing an active negative electrode material and a nanostructured metal oxide of titanium or aluminum prepared by pyrolysis in a mixing unit. The active negative electrode material is in powder form and includes carbon particles, silicon particles, silicon oxide particles, or any combination thereof.

[0260] Although the invention has been described with reference to particular embodiments, it should be understood that the invention is not limited to these embodiments and that many variations will fall within the scope of the invention as defined by the appended claims.

[0261] Reference numerals list

[0262] 10 Battery Cells

[0263] 100 Equipment powered by battery packs

[0264] 12 Positive collector

[0265] 14 Negative current collector

[0266] 16 Negative electrode

[0267] 18 Positive electrode

[0268] 20 Electrolytes

[0269] 22 Diaphragm

Claims

1. A method for preparing a coated active negative electrode material, characterized in that The coated active negative electrode material is obtained by subjecting the active negative electrode material and the nanostructured metal oxide of pyrolytically prepared aluminum oxide or titanium oxide or a mixture thereof to dry mixing under shearing conditions in a mixing unit, characterized in that the coated active negative electrode material is in the form of particles and the metal oxide has a particle size of 5 to 300 m 2 The BET surface area of ​​the particles is 1.3777:2014, and a mixture consisting of 5 wt. % of the particles and 95 wt. % of a 0.5 g / L sodium pyrophosphate aqueous solution is determined by static light scattering (SLS) after ultrasonic treatment at 25 ° C for 60 seconds, and has a unimodal and narrow particle size distribution, with an average aggregate diameter d 50 5 to 150 nm.

2. The method according to claim 1, characterized in that The pyrolyzed nanostructured metal oxide of aluminum oxide or titanium oxide is surface-treated to become hydrophobic by reacting hydroxyl groups of aluminum oxide or titanium oxide with silane to form -O-Si-R groups before the dry mixing, and the mixing unit has a specific electrical power of 0.05 to 1.5 kW per kg of the mixed negative electrode material.

3. The method according to claim 1 or 2, characterized in that: The average aggregate diameter d measured by static light scattering (SLS) of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution after ultrasonic treatment at 25° C. for 60 seconds is 50 It is 10 to 150 nm, preferably 20 to 100 nm.

4. The method according to claims 1 to 3, characterized in that Scanning electron microscopy with energy dispersive X-ray mapping of the coated active negative electrode material as disclosed in the specification provides complete and uniform coverage of the metal oxide around substantially all negative electrode particles.

5. The method according to claims 1 to 4, characterized in that The specific electric power of the mixing unit is 0.1 to 1000 kW, and the volume of the mixing unit is 0.1 L to 2.5 m 3 , and the speed of the mixing tool in the mixing unit is 5 to 30 m / s.

6. The method according to claims 1 to 5, characterized in that The span (d ) of the particles of the metal oxide and / or the particles of the mixed oxide containing aluminum or titanium measured by static light scattering (SLS) after a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution is treated with ultrasound at 25° C. for 60 seconds. 90 -d 10 ) / d 50 0.4 to 1.

2.

7. The method according to claims 1 to 6, characterized in that The active negative electrode material is in the form of a powder and comprises a powder and comprises carbon particles, silicon particles or silicon oxide particles or any combination thereof.

8. The method according to claims 1 to 7, characterized in that The coated active negative electrode material is further subjected to heat treatment after the dry mixing.

9. The method according to claims 1 to 8, characterized in that The proportion of the metal oxide in the coated active negative electrode material is 0.05 to 5 wt % based on the total weight of the coated mixed negative electrode material.

10. A coated active negative electrode material comprising an active negative electrode material of carbon particles, silicon particles or silicon oxide particles or any combination thereof and a coating of a nanostructured metal oxide of aluminum oxide, titanium oxide or a mixture thereof produced by pyrolysis on the surface of a mixed negative electrode material, wherein the coated active negative electrode material is in the form of particles and the metal oxide has a diameter of 5 to 300 m 2 The BET surface area of ​​the particles is 5 wt % and the mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution is measured by static light scattering (SLS) after ultrasonic treatment at 25° C. for 60 seconds, and the average aggregate diameter d 50 The nanostructured metal oxide is preferably 5 to 150 nm in diameter and the pyrolysis-produced nanostructured metal oxide is preferably surface treated to become hydrophobic by reacting hydroxyl groups of aluminum oxide or titanium oxide with silane to form -O-Si-R groups.

11. The coated active negative electrode material according to claim 10, characterized in that: As disclosed in the specification, the SEM-EDX profile of the coated active negative electrode material provides complete and uniform coverage of the metal oxide substantially around all negative electrode particles.

12. Coated active negative electrode material obtained by the process according to claims 1 to 9.

13. An active negative electrode material for a lithium ion battery comprising the coated active negative electrode material according to claims 10 to 12.

14. A lithium ion battery comprising the coated active negative electrode material according to claims 10 to 12.

15. Use of the coated active negative electrode material according to claims 10 to 12 as an active negative electrode material for lithium ion batteries.

16. Equipment comprising the lithium ion battery of claim 14, the equipment comprising electrical or electronic devices, the equipment comprising mobile phones, electronic watches, key fabs, laptop computers, desktop computers, computer tablets, power tools, vacuum cleaners, electric lawn mowers, appliances and electric vehicles.

Citation Information

Patent Citations

  • Silicon alloy nano-wire compound negative electrode material for lithium-ion battery and preparation method thereof

    CN106025242A

  • Protective coating for lithium-containing electrode and methods of making the same

    US20190363345A1

  • Lithium metal secondary battery featuring an anode-protecting layer

    US20190393543A1

  • Pyrogenically prepared, surface modified aluminum oxide

    WO2004108595A2

  • Method for manufacturing anodes for lithium-ion batteries

    WO2019215406A1